The effect of thermal insulation pads on heat flux, physical effort and perceived exertion during endurance exercise in cool environments - Wenger, S.; Csapo, R.; Hasler, M.; Gatterer, H.; Wright, T.; Nachbauer, W. (Fashion and Textiles, 2018)
To determine the effects of thermal insulation pads on clothing surface temperature, physical effort and perceived exertion during endurance exercise in cool environments two different pants (PCOOL, PINSUL) were designed: PCOOL (Insulation: 0.055 clo) was made of a thin base material while PINSUL (Insulation: 0.131 clo) featured additional insulation pads covering ~?30% of its surface, which were placed over the working leg muscles. Two sets of experiments were performed to compare both pants: Study A was completed in 10 active sportsmen who were instructed to run on a treadmill for 45 min at 60% of their maximal running velocity (vmax) at 7 °C. In study B, 8 endurance athletes completed the run with 70% vmax at 0 °C. Lower and upper body clothing surface temperatures (TLB, TUB), auditory canal temperature, blood lactate, heart rate, subjects´ loss of body mass and perceived exertion were measured. In both studies TLB was found to be lower with PINSUL, reflecting smaller heat loss due to the better thermal insulation. However no significant differences between pants were found for auditory canal temperature, blood lactate, heart rate, subjects´ loss of body mass or perceived exertion. Inserting insulation pads into sports apparel is a practicable approach to limit heat emission from working muscles during endurance exercise in the cold without impairing overall body-heat dissipation. However, under the environmental conditions and exercise intensities tested in this study, the thermal insulation of leg muscles failed to significantly affect parameters reflecting physical effort or perceived exertion